Bacterial blood stream infections and antibiogram among febrile patients at Bahir Dar Regional Health Research Laboratory Center, Ethiopia - Hailu, Derese; Abera, Bayeh; Yitayew, Gashaw; Mekonnen, Daniel; Derbie, Awoke (Ethiopian Journal of Science and Technology, 2025)
Bacterial blood stream infections (BSIs) are a common cause of morbidity and mortality. Prevailing data on bacterial species causing BSI and their antibiogram are essential for proper management of patients. A retrospective study was conducted on blood culture results that had been processed from March 2013 to January 2015 at Bahir Dar Regional Health Research Laboratory Center. In January 2015, data on age, sex of patients and bacterial isolates with antibiogram were extracted from registration log book. Blood stream causing bacteria were identified according to standard operational procedure for blood culture. Antimicrobial susceptibility tests were performed according to Kirby-Bauer disc diffusion methods. A total of 561 blood specimens were requested for blood culture. Of these, 220 (39.2%, 95% CI: 35.3-43.4%) blood cultures had aerobic bacterial growth. Gram negative bacterial isolates constituted 115 (52.3%) of the isolated bacteria. Staphylococcus aureus 50 (22.7%), coagulase negative staphylococci 35(15.9%), Klebsiella pneumoniae 35 (15.9%), Escherichia coli 19 (8.6%), Pseudomonas aeruginosa 15 (6.8%) and Acinetobacter species 13(5.9%) were the most dominant isolates. Overall, drug resistance for gram positive bacteria were 7 to 61% and for gram negatives 6.9 to 82.6%. Among the gram positive bacteria, high resistance levels were observed against penicillin (61%) and oxacillin (52.9%). The gram negative bacterial isolates showed 66 to 82.6% resistance to ampicillin, ceftriaxone and trimethoprim-sulfamethoxazole. The present study revealed that bacterial blood stream infections linked with high levels of drug resistance would pose a challenge in treatment of patients with BSIs. Hence, blood culture with antibiotic susceptibility tests could play key role for appropriate treatment of patients with bacterial blood stream infection.